On the (In)Comparability of the Interpretation of Art and Law - Tomáš Gábriš (Societas et Iurisprudentia)
In interpreting law as well as arts, the discursive approach is currently the one that fulfils Ernst H. Gombrich’s ideal of a hermeneutic compromise between two extremes – absolute knowledge (totality of knowledge) on the one hand and nihilistic relativism on the other. Discursiveness, as the ability to agree on certain starting points and frameworks of mutual communication, does not thereby represent claims to exclusive and sole objective correctness, but at the same time, it is also not about completely isolated and monological views. It is about views accepted in a certain social framework, within a certain discourse, conversation, or dialogue. This mechanism of interpretation is thereby accepted both in legal scholarship as well as in the history and theory of arts.